PERSEPSI GURU MI/SD TERHADAP PROFESIONALISME MELALUI KOLABORASI DAN TEACHER LEARNING COMUMUNICATIVE - safika, nailiyatul; Mazaya Shauma Yasyfa' Ardianti; Munawir (STKIP Subang, 2026)
Teacher professionalism is a crucial factor in improving the quality of education, particularly at the Madrasah Ibtidaiyah (MI) and elementary school (SD) levels. In practice, the development of professionalism is not solely dependent on individual capabilities but is also influenced by teacher collaboration and participation in Teacher Learning Communities. This study aims to analyze teachers’ perceptions of professionalism and examine the role of collaboration and Teacher Learning Communities in enhancing teacher professionalism. This research employs a qualitative descriptive approach. The subjects of the study are MI/SD teachers involved in collaborative activities and learning communities, with data collected through interviews, observations, and documentation. The findings reveal that teachers have a comprehensive understanding of professionalism, encompassing competencies, attitudes, and a commitment to continuous learning. Teacher collaboration through discussions, teamwork, and experience sharing has been shown to improve teaching competence and reflective practices. Furthermore, Teacher Learning Communities significantly contribute to fostering a sustainable learning culture and enhancing teachers’ confidence in teaching. Therefore, collaboration and Teacher Learning Communities play an essential role in supporting teacher professionalism at the MI/SD level.